High-thermal-conductivity organic silicon gel for IGBT (Insulated Gate Bipolar Translator) packaging and preparation method thereof

By introducing conjugated structures and rigid frameworks into the molecular chains of organosilicon gel and adding boron nitride nanosheets, a high thermal conductivity organosilicon gel was prepared, which solved the problem of low thermal conductivity and achieved improvements in high thermal conductivity, thermal stability and electrical strength, thus extending the service life of IGBT devices.

CN120865715APending Publication Date: 2025-10-31ZHEJIANG RONGTAI TECHNOLOGY ENTERPRISE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511272517.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-08
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

Existing silicone gels have low thermal conductivity, which cannot meet the high heat dissipation performance requirements of next-generation IGBT devices. Furthermore, the addition of thermally conductive fillers results in insufficient flexibility, affecting the vibration damping and protection effect.

Method used

High thermal conductivity organosilicon gels are prepared by introducing conjugated structures and/or rigid frameworks into the molecular chains of organosilicon gels and adding boron nitride nanosheets, using modified bisvinyl-terminated polydimethylsiloxane and vinyl silicone oil end-capping agents.

Benefits of technology

The thermal conductivity of the silicone gel is significantly improved to 0.25-0.27 W/m·K, while the thermal stability and electrical strength are improved, providing good insulation and vibration protection, and extending the service life of IGBT devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of organic silicon packaging materials, in particular to high-thermal-conductivity organic silicon gel for IGBT packaging and a preparation method of the high-thermal-conductivity organic silicon gel. The invention relates to a high thermal conductivity type organosilicon gel for IGBT packaging. The high thermal conductivity type organosilicon gel is composed of a component A and a component B, wherein the molar ratio of Si-H to Si-Vi is (0.30-0.50): 1; the modified divinyl-terminated polydimethylsiloxane in the component A and the component B is divinyl-terminated polydimethylsiloxane of which the side chain contains at least one of an aromatic ring, a fluorine element and an aliphatic ring and / or divinyl-terminated polydimethylsiloxane of which the main chain contains a liquid crystal block. The heat conductivity coefficient of the organosilicone gel can reach 0.25-0.27 W / mK, the heat conductivity coefficient of the organosilicone gel is increased by more than or equal to 20% compared with that of conventional organosilicone gel, and the organosilicone gel has good heat-resistant stability and electrical strength, has better insulation protection and vibration reduction protection effects, and is beneficial to prolonging the service life of an IGBT (Insulated Gate Bipolar Translator) device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of silicone encapsulation materials technology, and in particular to a high thermal conductivity silicone gel for IGBT encapsulation and its preparation method. Background Technology

[0002] Wire bonding is currently the most widely used chip interconnect technology in industry. Electrical connections between IGBT chips, between IGBT chip terminals and diode chips, and between chip terminals and insulating substrates are generally achieved using wire bonding technology. Wire bonding interconnects chips, forming circuits, and is one of the main methods for achieving internal electrical interconnection in IGBT power devices. Currently, commonly used wires include aluminum wire bonding, copper wire bonding, silver wire bonding, and gold wire bonding.

[0003] Organosilicon gel is a special type of silicone rubber with a "solid-liquid coexistence" structure. It possesses advantages such as high elasticity, low stress, extremely low Young's modulus, and excellent heat resistance, making it one of the most popular IGBT encapsulation materials currently available. Encapsulating IGBT chips with organosilicon gel provides better vibration damping protection for IGBT devices, while also enabling stable operation under conditions of large temperature fluctuations and strong vibrations. This effectively reduces the structural damage to the bonding wires in IGBT devices caused by electrical and thermal stress, extending the lifespan of the IGBT devices. The bonding wires generate heat during circuit conduction; this heat accumulates within the organosilicon gel encapsulation material, causing its temperature to rise. Excessive cross-linking and hardening of the organosilicon gel due to thermal oxidation can negatively impact its protective function for the IGBT encapsulation.

[0004] The thermal conductivity of pure silicone gel encapsulation is relatively low, ranging from 0.15 to 0.22 W / m•K. One method to improve the thermal conductivity of silicone gel encapsulation is to add thermally conductive fillers. However, for silicone gels used in IGBT chip encapsulation, adding fillers leads to an excessively large taper, resulting in insufficient flexibility to meet the IGBT chip encapsulation requirements and affecting the vibration damping protection of the IGBT device. With the increasing power of next-generation IGBT devices, higher demands are placed on the heat dissipation performance of silicone gel encapsulation materials for these devices. Therefore, there is an urgent need for a high thermal conductivity silicone gel for IGBT encapsulation and its preparation method. Summary of the Invention

[0005] To address the high heat dissipation performance requirements of silicone gel encapsulation materials for next-generation IGBT devices, this invention provides a high thermal conductivity silicone gel for IGBT encapsulation and its preparation method.

[0006] The high thermal conductivity silicone gel for IGBT packaging provided by this invention is achieved through the following technical solution: A high thermal conductivity silicone gel for IGBT encapsulation comprises component A and component B, with a Si-H to Si-Vi molar ratio of (0.30-0.50):1. Component A is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane, 50-200 parts of modified divinyl-terminated polydimethylsiloxane, and 0.5-3 parts of platinum catalyst. Component B is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane, 50-100 parts of modified divinyl-terminated polydimethylsiloxane, and 0.5-3 parts of platinum catalyst. The composition comprises: 8-25 parts of divinyl-terminated polydimethylsiloxane, 1-4 parts of hydrogen-terminated polydimethylsiloxane with hydrogen groups on the end, 0.05-0.25 parts of inhibitor, and 0-0.5 parts of nano-inorganic filler; wherein the modified divinyl-terminated polydimethylsiloxane in components A and B is a divinyl-terminated polydimethylsiloxane with at least one of aromatic ring, fluorine element, and aliphatic ring in the side chain and / or a divinyl-terminated polydimethylsiloxane with liquid crystal blocks in the main chain.

[0007] This invention introduces conjugated structures and / or rigid frameworks into the molecular chain of silicone gel, resulting in a ≥20% improvement in thermal conductivity compared to conventional silicone gels, with a thermal conductivity reaching 0.25-0.27 W / m•K. Furthermore, the introduction of conjugated structures, fluorine elements, and / or rigid frameworks into the molecular chain structure of the silicone gel further improves its thermal stability and electrical strength, providing excellent and long-lasting insulation and vibration damping protection for IGBT devices, thereby extending the lifespan of IGBT devices.

[0008] Preferably, the modified bisvinyl-terminated polydimethylsiloxane is made of fluorinated silane monomer, dimethoxysilane monomer, and vinyl silicone oil end-capping agent.

[0009] Preferably, the fluorinated silane monomer is any one or a combination of multiple of 3,3,3-trifluoropropylmethyldimethoxysilane, 1H,1H,2H,2H-perfluorooctylmethyldimethoxysilane, and dodecafluoroheptylpropylmethyldimethoxysilane.

[0010] Preferably, the dimethoxysilane monomer is any one or a combination of multiple of dimethyldimethoxysilane, isobutylisopropyldimethoxysilane, phenylmethyldimethoxysilane, and cyclohexylmethyldimethoxysilane.

[0011] Preferably, the vinyl silicone oil end-capping agent is 3-(methoxydimethylsilyl)propyl acrylate and / or vinyldimethylethoxysilane.

[0012] It should be noted that the amount of fluorinated silane monomer used will affect the adhesion and potting effect. The molar ratio of the fluorinated silane monomer to the dimethoxysilane monomer should be controlled at 1:(3-7) to improve the overall heat resistance and electrical strength, while ensuring good adhesion strength and potting effect.

[0013] Preferably, the divinyl-terminated polydimethylsiloxane containing liquid crystal blocks in the main chain is made of diacyl chloride-terminated polydimethylsiloxane, dihydroxyl-terminated polydimethylsiloxane, N-(4-hydroxybenzyl)-4-hydroxy-2-trifluoroacetanilide, and vinyl silicone oil end-capping agent.

[0014] Preferably, the diacyl chloride-terminated polydimethylsiloxane is prepared by a hydrosilylation reaction of dihydro-terminated polydimethylsiloxane and methacryl chloride; the vinyl silicone oil end-capping agent is 3-(methoxydimethylsilyl)propyl acrylate and / or vinyldimethylethoxysilane.

[0015] Preferably, the molar ratio of the diacyl chloride-terminated polydimethylsiloxane to the sum of the molar amounts of the dihydroxyl-terminated polydimethylsiloxane and N-(4-hydroxybenzyl)-4-hydroxy-2-trifluoroacetanilide is (1.01-1.02):1; and the molar ratio of the dihydroxyl-terminated polydimethylsiloxane to N-(4-hydroxybenzyl)-4-hydroxy-2-trifluoroacetanilide is (1-3):1.

[0016] Preferably, component A is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane, 100 parts of modified divinyl-terminated polydimethylsiloxane, and 1-2 parts of platinum catalyst; component B is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane, 100 parts of modified divinyl-terminated polydimethylsiloxane, 12-16 parts of hydrogen-terminated polydimethylsiloxane, 2.0-2.5 parts of hydrogen-terminated polydimethylsiloxane with hydrogen groups on the end side, 0.10-0.20 parts of inhibitor, and 0.25-0.5 parts of nano-inorganic filler; wherein the nano-inorganic filler is boron nitride nanosheets.

[0017] Adding an appropriate amount of boron nitride nanosheets to the formulation can improve the overall yellowing resistance without affecting the cone penetration of the silicone gel, giving the silicone gel good thermal conductivity while also possessing good yellowing resistance, thermal stability and electrical strength.

[0018] The present invention provides a method for preparing a high thermal conductivity silicone gel for IGBT packaging, which is achieved through the following technical solution: A method for preparing a high thermal conductivity silicone gel for IGBT packaging includes the following steps: Step 1: Preparation of modified bisvinyl-terminated polydimethylsiloxane; Step 2, Preparation of component A: 100 parts of bisvinyl-terminated polydimethylsiloxane, 50-200 parts of modified bisvinyl-terminated polydimethylsiloxane, and 0.5-3 parts of platinum catalyst are stirred evenly under an inert atmosphere and then degassed under vacuum to obtain component A. Preparation of component B: 100 parts of bisvinyl-terminated polydimethylsiloxane, 50-100 parts of modified bisvinyl-terminated polydimethylsiloxane, 8-25 parts of hydrogen-terminated polydimethylsiloxane, 1-4 parts of hydrogen-terminated polydimethylsiloxane with hydrogen groups on the end side, 0.05-0.25 parts of inhibitor, and 0-0.5 parts of nano-inorganic filler were stirred evenly under an inert atmosphere and then vacuum degassed to obtain component B; Step 3: Mix component A and component B evenly to obtain the finished high thermal conductivity silicone gel for IGBT packaging.

[0019] The preparation method of the high thermal conductivity silicone gel for IGBT packaging is relatively mature and easy to achieve large-scale production.

[0020] In summary, the present invention has the following advantages: 1. This invention introduces conjugated structures and / or rigid frameworks into the molecular chain of silicone gel, resulting in a ≥20% increase in thermal conductivity compared to conventional silicone gels, with a thermal conductivity reaching 0.25-0.27 W / m•K. Simultaneously, the introduction of conjugated structures and / or rigid frameworks into the molecular chain structure of the silicone gel improves its thermal stability and electrical strength, providing excellent and long-lasting insulation and vibration damping protection for IGBT devices, thereby extending the service life of IGBT devices.

[0021] 2. In this invention, the introduction of a conjugated structure (benzene ring) into the molecular chain of the organosilicon gel can affect the overall yellowing resistance. In this invention, the addition of 1-2 parts of boron nitride nanosheets to the organosilicon gel improves the overall yellowing resistance, giving the organosilicon gel good thermal conductivity while also possessing good yellowing resistance, thermal stability and electrical strength.

[0022] 3. The preparation method of the present invention is relatively mature, has low requirements for production equipment, and is easy to achieve large-scale production. Detailed Implementation

[0023] To further understand the inventiveness and technical advancements of this invention, the preferred embodiments of this invention will be discussed in detail below with reference to examples and comparative examples.

[0024] Example: A high thermal conductivity silicone gel for IGBT packaging is composed of component A and component B, with a Si-H to Si-Vi molar ratio of (0.30-0.50):1.

[0025] Component A is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane, 50-200 parts of modified divinyl-terminated polydimethylsiloxane, and 0.5-3 parts of platinum catalyst. Preferably, component A is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane, 100 parts of modified divinyl-terminated polydimethylsiloxane, and 1-2 parts of platinum catalyst.

[0026] Component B is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane, 50-100 parts of modified divinyl-terminated polydimethylsiloxane, 8-25 parts of hydrogen-terminated polydimethylsiloxane, 1-4 parts of hydrogen-terminated polydimethylsiloxane with end-group hydrogen groups, 0.05-0.25 parts of inhibitor, and 0-0.5 parts of nano-inorganic filler. Preferably, component B is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane, 100 parts of modified divinyl-terminated polydimethylsiloxane, 12-16 parts of hydrogen-terminated polydimethylsiloxane, 2.0-2.5 parts of hydrogen-terminated polydimethylsiloxane with end-group hydrogen groups, 0.10-0.20 parts of inhibitor, and 0.25-0.5 parts of nano-inorganic filler.

[0027] The nano-inorganic filler is boron nitride nanosheets, and the surface of the boron nitride nanosheets is hydrophobically modified.

[0028] The inhibitor is at least one of the following: 1-ethynylcyclohexanol, (S)-5-phenyl-1-pentyn-3-ol, 3-octyl-1-butyn-3-ol, and 3-methyl-1-butyn-3-ol.

[0029] The modified divinyl-terminated polydimethylsiloxane in component A and component B is a divinyl-terminated polydimethylsiloxane with at least one of aromatic rings, fluorine elements, and aliphatic rings in the side chain and / or a divinyl-terminated polydimethylsiloxane with liquid crystal blocks in the main chain.

[0030] Divinyl-terminated polydimethylsiloxane with a side chain containing at least one of aromatic rings, fluorine, and aliphatic rings is produced by conventional polymerization of a fluorinated silane monomer, a dimethoxysilane monomer, and a vinyl silicone oil end-capping agent, wherein the molar ratio of the fluorinated silane monomer to the dimethoxysilane monomer is 1:(3-7). The fluorinated silane monomer is any one or a combination of multiples of 3,3,3-trifluoropropylmethyldimethoxysilane, 1H,1H,2H,2H-perfluorooctylmethyldimethoxysilane, and dodecafluoroheptylpropylmethyldimethoxysilane. The dimethoxysilane monomer is any one or a combination of multiples of dimethyldimethoxysilane, isobutylisopropyldimethoxysilane, phenylmethyldimethoxysilane, and cyclohexylmethyldimethoxysilane. The vinyl silicone oil end-capping agent is 3-(methoxydimethylsilyl)propyl acrylate and / or vinyldimethylethoxysilane.

[0031] Divinyl-terminated polydimethylsiloxane containing liquid crystal blocks in its main chain is prepared by conventional polymerization reactions of diacyl chloride-terminated polydimethylsiloxane, dihydroxyl-terminated polydimethylsiloxane, N-(4-hydroxybenzyl)-4-hydroxy-2-trifluoroacetanilide, and vinyl silicone oil end-capping agent. Diacyl chloride-terminated polydimethylsiloxane is prepared by hydrosilylation reaction of dihydrogen-terminated polydimethylsiloxane and methacryloyl chloride. The vinyl silicone oil end-capping agent is 3-(methoxydimethylsilyl)propyl acrylate and / or vinyldimethylethoxysilane. The molar ratio of diacyl chloride-terminated polydimethylsiloxane to the sum of the molar amounts of dihydroxyl-terminated polydimethylsiloxane and N-(4-hydroxybenzyl)-4-hydroxy-2-trifluoroacetanilide is (1.01-1.02): and the molar ratio of dihydroxyl-terminated polydimethylsiloxane to N-(4-hydroxybenzyl)-4-hydroxy-2-trifluoroacetanilide is (1-3):1.

[0032] A method for preparing a high thermal conductivity silicone gel for IGBT packaging includes the following steps: Step 1: Preparation of modified bisvinyl-terminated polydimethylsiloxane; Step 2, Preparation of component A: 100 parts of bisvinyl-terminated polydimethylsiloxane, 50-200 parts of modified bisvinyl-terminated polydimethylsiloxane, and 0.5-3 parts of platinum catalyst are stirred evenly under an inert atmosphere and then degassed under vacuum to obtain component A. Preparation of component B: 100 parts of bisvinyl-terminated polydimethylsiloxane, 50-100 parts of modified bisvinyl-terminated polydimethylsiloxane, 8-25 parts of hydrogen-terminated polydimethylsiloxane, 1-4 parts of hydrogen-terminated polydimethylsiloxane with hydrogen groups on the end side, 0.05-0.25 parts of inhibitor, and 0-0.5 parts of nano-inorganic filler were stirred evenly under an inert atmosphere and then vacuum degassed to obtain component B; Step 3: Mix component A and component B evenly to obtain the finished high thermal conductivity silicone gel for IGBT packaging.

[0033] Preparation Example 1: The modified bisvinyl-terminated polydimethylsiloxane was prepared from 3,3,3-trifluoropropylmethyldimethoxysilane (CAS No.: 358-67-8), dimethyldimethoxysilane (CAS No.: 1112-39-6), phenylmethyldimethoxysilane (CAS No.: 3027-21-2), and vinyldimethylethoxysilane (CAS No.: 5356-83-2). The molar ratio of 3,3,3-trifluoropropylmethyldimethoxysilane to dimethyldimethoxysilane and phenylmethyldimethoxysilane was 1:1:3.5.

[0034] The preparation method of modified bisvinyl-terminated polydimethylsiloxane is as follows: Step 1: Prepare the hydrolysate of 3,3,3-trifluoropropylmethyldimethoxysilane: Add 202.2g of 3,3,3-trifluoropropylmethyldimethoxysilane, 727.9g of ethanol and 80.9g of deionized water to a 2L experimental reactor. Stir at 200rpm at room temperature. Add 0.2mol / L dilute hydrochloric acid to adjust the pH of the system to 3.5 to obtain the hydrolysate of 3,3,3-trifluoropropylmethyldimethoxysilane. Preparation of phenylmethyldimethoxysilane hydrolysate: Add 182.3g of phenylmethyldimethoxysilane, 656.3g of ethanol and 15.4g of deionized water to a 2L experimental reactor, stir at 200rpm at room temperature, and add 0.2mol / L dilute hydrochloric acid to adjust the pH of the system to 3.5 to obtain the phenylmethyldimethoxysilane hydrolysate; Preparation of dimethyldimethoxysilane hydrolysate: Add 422.1g of dimethyldimethoxysilane, 1519.6g of ethanol and 24.3g of deionized water to a 5L experimental reactor, stir at 200rpm at room temperature, and add 0.2mol / L dilute hydrochloric acid to adjust the pH of the system to 3.5 to obtain dimethyldimethoxysilane hydrolysate; Preparation of vinyldimethylethoxysilane hydrolysate: Add 130.3g of vinyldimethylethoxysilane, 468.9g of ethanol and 10.1g of deionized water to a 1L experimental reactor, stir at 200rpm at room temperature, and add 0.2mol / L dilute hydrochloric acid to adjust the pH of the system to 3.5 to obtain vinyldimethylethoxysilane hydrolysate; Step 2: Vacuum-pumped dimethyldimethoxysilane hydrolysate and phenylmethyldimethoxysilane hydrolysate were vacuum-pumped into a 10L reactor. The reactor was heated to 60°C in a water bath, and stirred at 200 rpm. The prepared 3,3,3-trifluoropropylmethyldimethoxysilane hydrolysate was added to the 10L reactor at a rate of 10 g / min. After the addition was complete, the reactor was kept at 60°C for 30 minutes. The prepared vinyldimethylethoxysilane hydrolysate was added to the 10L reactor at a rate of 30 g / min. After the addition was complete, the reactor was kept at 60°C for 30 minutes. The temperature was then raised to 80°C and the reactor was reacted for 3 hours. Ethanol and methanol were distilled off simultaneously. After the reaction was completed, the mixture was cooled to room temperature, sodium hydroxide was added to neutralize the hydrochloric acid to neutral, the mixture was transferred to a separatory funnel, allowed to stand and separate into layers, the bottom aqueous phase was discarded, and the upper oily liquid was retained. The mixture was washed several times with deionized water until no chloride ions were present in the product. Unreacted small molecule monomers were removed by vacuum distillation to obtain a colorless and transparent product with a viscosity of 2024 cSt and a vinyl content of 0.08 mmoles / g.

[0035] Preparation Example 2: Modified divinyl-terminated polydimethylsiloxane was prepared from diacyl chloride-terminated polydimethylsiloxane, dihydroxyl-terminated polydimethylsiloxane, and N-(4-hydroxybenzyl)-4-hydroxy-2-trifluoroacetanilide vinyl silicone oil end-capping agent. The molar ratio of the diacyl chloride-terminated polydimethylsiloxane to the sum of the molar amounts of dihydroxyl-terminated polydimethylsiloxane and N-(4-hydroxybenzyl)-4-hydroxy-2-trifluoroacetanilide was (1.01-1.02):1. The molar ratio of dihydroxyl-terminated polydimethylsiloxane to N-(4-hydroxybenzyl)-4-hydroxy-2-trifluoroacetanilide was 3:1.

[0036] The preparation method of modified bisvinyl-terminated polydimethylsiloxane is as follows: Step 1: Preparation of diacyl chloride-terminated polydimethylsiloxane: Dissolve 72.6g of dihydrogen-terminated polydimethylsiloxane (Andisil CE-4 chain extender, SiH content 2.55mmoles / g) and 20.9g of methacryloyl chloride (CAS No.: 920-46-7) in 200mL of N,N-dimethylformamide DMF, add 0.5g of platinum catalyst (Karstedt, 5000ppm, provided by Dongguan Dongsheng Synthetic Materials Co., Ltd.), heat to 75℃ for 60 minutes, and remove unreacted small molecule monomers by vacuum distillation to obtain diacyl chloride-terminated polydimethylsiloxane; N-(4-hydroxybenzyl)-4-hydroxy-2-trifluoroacetanilide is prepared by hydrolyzing N-(4-methoxybenzyl)-4-chloro-2-trifluoroacetanilide (CAS No.: 173676-54-5) in an aqueous sodium hydroxide solution. 3.44 parts by weight of N-(4-methoxybenzyl)-4-chloro-2-trifluoroacetanilide and 20 parts by weight of a 25 wt% aqueous sodium hydroxide solution are added to a high-pressure reactor. The mixture is stirred at 200 rpm, heated to 240°C, and pressurized to 20 MPa for 2 hours. The temperature and pressure are then lowered to room temperature and pressure, and 10 wt% sulfuric acid solution is added to adjust the pH to 1.0. The mixture is then heated to 80°C and reacted for 60 minutes. After acidification, N,N-dimethylformamide is used for extraction. The resulting DMF extract is then subjected to vacuum distillation to remove the DMF, yielding N-(4-hydroxybenzyl)-4-hydroxy-2-trifluoroacetanilide. Preparation of vinyldimethylethoxysilane hydrolysate: Add 6.5g of vinyldimethylethoxysilane, 23.5g of ethanol and 2.6g of deionized water to a 100mL beaker, stir at 200rpm at room temperature, and add 5wt% acetic acid aqueous solution to adjust the pH of the system to 3.5 to obtain vinyldimethylethoxysilane hydrolysate; Step two, prepare by weighing 9.46g of diacyl chloride-terminated polydimethylsiloxane and 7.50g of bihydroxyl-terminated silicone oil IOTA 2110 (number average molecular weight 1000, hydroxyl value 112.2). (mg KOH / g, provided by Anhui Aiyota Silicon Oil Co., Ltd.) 8.1g of N-(4-hydroxybenzyl)-4-hydroxy-2-trifluoroacetanilide, 72g of ethanol, 8g of deionized water, and 4.2g of acid-binding agent triethylamine were poured into a three-necked flask. Under magnetic stirring at 180r / min, the temperature was raised to 65℃ and maintained at 65℃ for 90 minutes. The vinyl dimethyl ethoxysilane hydrolysate prepared in step one was added, and the end-capping reaction was carried out at 65℃ for 60 minutes. After the reaction was completed, the mixture was allowed to stand and separate into layers. The lower aqueous phase was removed, and the resulting transparent product was subjected to vacuum distillation to remove unreacted small molecule monomers, yielding a transparent divinyl-terminated polydimethylsiloxane with liquid crystal blocks in the main chain, with a viscosity of 4168cSt and a vinyl content of 0.06mmoles / g.

[0037] Example 1: A high thermal conductivity silicone gel for IGBT packaging is composed of component A and component B. The molar ratio of Si-H to Si-Vi in the high thermal conductivity silicone gel for IGBT packaging is 0.30:1.

[0038] Component A is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (AndisilVS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 100 parts of the modified divinyl-terminated polydimethylsiloxane from Preparation Example 1 (vinyl content 0.08 mmoles / g), and 2 parts of platinum catalyst (Karstedt, 5000 ppm, provided by Dongguan Dongsheng Synthetic Materials Co., Ltd.).

[0039] Component B is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (Andisil VS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 100 parts of the modified divinyl-terminated polydimethylsiloxane in Preparation Example 1 (vinyl content 0.08 mmoles / g), 10.1 parts of hydrogen-terminated polydimethylsiloxane (Andisil CE-13 chain extender, SiH content 1.37 mmoles / g), 2.0 parts of hydrogen-terminated polydimethylsiloxane with end-hydrogen groups (Andisil XL-1340 crosslinking agent, SiH content 3.0 mmoles / g), 0.15 parts of (S)-5-phenyl-1-pentyn-3-ol (CAS No.: 183904-28-1), and 0.5 parts of boron nitride nanosheets.

[0040] The preparation method of boron nitride nanosheets has been disclosed in our company's 2024 application for a high-temperature resistant silicone gel for IGBT encapsulation and its preparation method (application number 2024117339863). To facilitate the reader's understanding of the technical solution, the preparation method of boron nitride nanosheets is described in this invention. The specific preparation method is as follows: S1. First, place the hexagonal nitride nanosheets (hexagonal nitride nanosheets with the product number XT-BN-01 from Shanghai Xiangtian Nanomaterials Co., Ltd., with a specification of 120nm) at 200℃ for 2 hours for thermal activation treatment, and set them aside for later use; S2. The thermally activated hexagonal nitride nanosheets were added to a planetary ball mill and dry ball milled at 80 rpm for 30 min. S3. The ball-milled hexagonal nitride nanosheets were subjected to low-temperature plasma modification treatment. Specifically, the hexagonal nitride nanosheets refined by dry ball milling in S2 were placed in a plasma surface treatment instrument and subjected to low-temperature plasma treatment with ozone at 0-4℃ for 8 min. The plasma generator frequency was 40KHz and the gas flow rate under the float needle valve flow controller was 1.5L / min to obtain hydroxylated modified hexagonal nitride nanosheets. S4. Add 5g of hydroxylated modified hexagonal nitride nanosheets and 0.05g of polymerization inhibitor benzoquinone to 100g of 4wt% aqueous solution of dimethoxymethyl vinylsilane (CAS No. 16753-62-1), mix evenly, and then perform ultrasonic dispersion treatment for 30min at an ultrasonic frequency of 40kHz and a power of 600W to obtain a dispersion. S5. Filter the obtained dispersion, place the obtained solid in a vacuum drying oven, dry at 105℃ for 4 hours under an internal pressure of 10Pa to obtain solid material, place the obtained solid material in a planetary ball mill for fine ball milling treatment, ball mill at 60rpm for 30min to obtain hexagonal nitride nanosheets with surface grafted vinylsilane.

[0041] A method for preparing a high thermal conductivity silicone gel for IGBT packaging includes the following steps: Step 1, Preparation of modified bisvinyl-terminated polydimethylsiloxane, see Preparation Example 1; Step 2, Preparation of Component A: Nitrogen gas was introduced into the reactor to purge the air. Then, 100 parts of divinyl-terminated polydimethylsiloxane (Andisil VS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 100 parts of the modified divinyl-terminated polydimethylsiloxane from Preparation Example 1 (vinyl content 0.11 mmoles / g), and 2 parts of platinum catalyst (Karstedt, 5000 ppm) were added to the reactor. The mixture was stirred at 240 rpm for 30 minutes under a nitrogen atmosphere, followed by vacuum degassing for 30 minutes. Component A was then discharged. Preparation of Component B: Nitrogen gas was introduced into the reactor to purge the air. Then, 100 parts of divinyl-terminated polydimethylsiloxane (Andisil VS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 100 parts of the modified divinyl-terminated polydimethylsiloxane from Preparation Example 1 (vinyl content 0.11 mmoles / g), 16.5 parts of hydrogen-terminated polydimethylsiloxane (Andisil XL-1B chain extender, SiH content 0.95 mmoles / g), and 2.0 parts of hydrogen-terminated polydimethylsiloxane with end-group hydrogen groups (Andisil XL-1340 crosslinking agent, SiH...) were added. 0.15 parts of (S)-5-phenyl-1-pentyn-3-ol (CAS No.: 183904-28-1) and 0.5 parts of boron nitride nanosheets were added to a reactor and stirred at 240 rpm for 30 minutes under a nitrogen atmosphere. Then, the mixture was degassed under vacuum for 30 minutes, and component B was discharged. Step 3: When using, mix component A and component B at a mass ratio of 1:1 until homogeneous to obtain the finished high thermal conductivity silicone gel for IGBT packaging. The curing parameters are as follows: Pour the finished high thermal conductivity silicone gel for IGBT packaging into a dried mold, and vacuum degas at a pressure of 0.08–0.1 MPa for 10 minutes. Then cure at 120°C for 1 hour. Demold to obtain the cured high thermal conductivity silicone gel for IGBT packaging.

[0042] The difference between Example 2 and Example 1 is that: a high thermal conductivity silicone gel for IGBT packaging is composed of component A and component B, and the molar ratio of Si-H and Si-Vi in the high thermal conductivity silicone gel for IGBT packaging is 0.40:1.

[0043] Component A is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (AndisilVS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 100 parts of the modified divinyl-terminated polydimethylsiloxane from Preparation Example 1 (vinyl content 0.08 mmoles / g), and 2 parts of platinum catalyst (Karstedt, 5000 ppm, provided by Dongguan Dongsheng Synthetic Materials Co., Ltd.).

[0044] Component B is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (Andisil VS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 100 parts of the modified divinyl-terminated polydimethylsiloxane in Preparation Example 1 (vinyl content 0.08 mmoles / g), 14.9 parts of hydrogen-terminated polydimethylsiloxane (Andisil CE-13 chain extender, SiH content 1.37 mmoles / g), 2.0 parts of hydrogen-terminated polydimethylsiloxane with end-hydrogen groups (Andisil XL-1340 crosslinking agent, SiH content 3.0 mmoles / g), 0.15 parts of (S)-5-phenyl-1-pentyn-3-ol (CAS No.: 183904-28-1), and 0.5 parts of boron nitride nanosheets.

[0045] The difference between Example 3 and Example 1 is that: a high thermal conductivity silicone gel for IGBT packaging is composed of component A and component B, and the molar ratio of Si-H and Si-Vi in the high thermal conductivity silicone gel for IGBT packaging is 0.50:1.

[0046] Component A is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (AndisilVS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 100 parts of the modified divinyl-terminated polydimethylsiloxane from Preparation Example 1 (vinyl content 0.08 mmoles / g), and 2 parts of platinum catalyst (Karstedt, 5000 ppm, provided by Dongguan Dongsheng Synthetic Materials Co., Ltd.).

[0047] Component B is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (Andisil VS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 100 parts of the modified divinyl-terminated polydimethylsiloxane in Preparation Example 1 (vinyl content 0.08 mmoles / g), 19.7 parts of hydrogen-terminated polydimethylsiloxane (Andisil CE-13 chain extender, SiH content 1.37 mmoles / g), 2.0 parts of hydrogen-terminated polydimethylsiloxane with end-group hydrogen groups (Andisil XL-1340 crosslinking agent, SiH content 3.0 mmoles / g), 0.15 parts of (S)-5-phenyl-1-pentyn-3-ol (CAS No.: 183904-28-1), and 0.5 parts of boron nitride nanosheets.

[0048] The difference between Example 4 and Example 1 is that: a high thermal conductivity silicone gel for IGBT packaging is composed of component A and component B, and the molar ratio of Si-H and Si-Vi in the high thermal conductivity silicone gel for IGBT packaging is 0.30:1.

[0049] Component A is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (AndisilVS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 100 parts of the modified divinyl-terminated polydimethylsiloxane from Preparation Example 2 (vinyl content 0.06 mmoles / g), and 2 parts of platinum catalyst (Karstedt, 5000 ppm, provided by Dongguan Dongsheng Synthetic Materials Co., Ltd.).

[0050] Component B is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (Andisil VS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 100 parts of the modified divinyl-terminated polydimethylsiloxane from Preparation Example 2 (vinyl content 0.06 mmoles / g), 9.2 parts of hydrogen-terminated polydimethylsiloxane (Andisil CE-13 chain extender, SiH content 1.37 mmoles / g), 2.0 parts of hydrogen-terminated polydimethylsiloxane with end-group hydrogen groups (Andisil XL-1340 crosslinking agent, SiH content 3.0 mmoles / g), 0.15 parts of (S)-5-phenyl-1-pentyn-3-ol (CAS No.: 183904-28-1), and 0.5 parts of boron nitride nanosheets.

[0051] The difference between Example 5 and Example 1 is that: a high thermal conductivity silicone gel for IGBT packaging is composed of component A and component B, and the molar ratio of Si-H and Si-Vi in the high thermal conductivity silicone gel for IGBT packaging is 0.40:1.

[0052] Component A is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (AndisilVS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 100 parts of the modified divinyl-terminated polydimethylsiloxane from Preparation Example 2 (vinyl content 0.06 mmoles / g), and 2 parts of platinum catalyst (Karstedt, 5000 ppm, provided by Dongguan Dongsheng Synthetic Materials Co., Ltd.).

[0053] Component B is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (Andisil VS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 100 parts of the modified divinyl-terminated polydimethylsiloxane from Preparation Example 2 (vinyl content 0.06 mmoles / g), 13.7 parts of hydrogen-terminated polydimethylsiloxane (Andisil CE-13 chain extender, SiH content 1.37 mmoles / g), 2.0 parts of hydrogen-terminated polydimethylsiloxane with end-hydrogen groups (Andisil XL-1340 crosslinking agent, SiH content 3.0 mmoles / g), 0.15 parts of (S)-5-phenyl-1-pentyn-3-ol (CAS No.: 183904-28-1), and 0.5 parts of boron nitride nanosheets.

[0054] The difference between Example 6 and Example 1 is that: a high thermal conductivity silicone gel for IGBT packaging is composed of component A and component B, and the molar ratio of Si-H and Si-Vi in the high thermal conductivity silicone gel for IGBT packaging is 0.50:1.

[0055] Component A is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (AndisilVS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 100 parts of the modified divinyl-terminated polydimethylsiloxane from Preparation Example 2 (vinyl content 0.06 mmoles / g), and 2 parts of platinum catalyst (Karstedt, 5000 ppm, provided by Dongguan Dongsheng Synthetic Materials Co., Ltd.).

[0056] Component B is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (Andisil VS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 100 parts of the modified divinyl-terminated polydimethylsiloxane in Preparation Example 2 (vinyl content 0.06 mmoles / g), 18.2 parts of hydrogen-terminated polydimethylsiloxane (Andisil CE-13 chain extender, SiH content 1.37 mmoles / g), 2.0 parts of hydrogen-terminated polydimethylsiloxane with end-hydrogen groups (Andisil XL-1340 crosslinking agent, SiH content 3.0 mmoles / g), 0.15 parts of (S)-5-phenyl-1-pentyn-3-ol (CAS No.: 183904-28-1), and 0.5 parts of boron nitride nanosheets.

[0057] The difference between Example 7 and Example 1 is that: a high thermal conductivity silicone gel for IGBT packaging is composed of component A and component B, and the molar ratio of Si-H and Si-Vi in the high thermal conductivity silicone gel for IGBT packaging is 0.30:1.

[0058] Component A is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (AndisilVS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 100 parts of the modified divinyl-terminated polydimethylsiloxane from Preparation Example 1 (vinyl content 0.08 mmoles / g), and 2 parts of platinum catalyst (Karstedt, 5000 ppm, provided by Dongguan Dongsheng Synthetic Materials Co., Ltd.).

[0059] Component B is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (Andisil VS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 100 parts of the modified divinyl-terminated polydimethylsiloxane in Preparation Example 2 (vinyl content 0.06 mmoles / g), 9.7 parts of hydrogen-terminated polydimethylsiloxane (Andisil CE-13 chain extender, SiH content 1.37 mmoles / g), 2.0 parts of hydrogen-terminated polydimethylsiloxane with end-hydrogen groups (Andisil XL-1340 crosslinking agent, SiH content 3.0 mmoles / g), 0.15 parts of (S)-5-phenyl-1-pentyn-3-ol (CAS No.: 183904-28-1), and 0.5 parts of boron nitride nanosheets.

[0060] The difference between Example 8 and Example 1 is that: a high thermal conductivity silicone gel for IGBT packaging is composed of component A and component B, and the molar ratio of Si-H and Si-Vi in the high thermal conductivity silicone gel for IGBT packaging is 0.30:1.

[0061] Component A is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (AndisilVS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 50 parts of the modified divinyl-terminated polydimethylsiloxane from Preparation Example 1 (vinyl content 0.08 mmoles / g), and 2 parts of platinum catalyst (Karstedt, 5000 ppm, provided by Dongguan Dongsheng Synthetic Materials Co., Ltd.).

[0062] Component B is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (Andisil VS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 100 parts of the modified divinyl-terminated polydimethylsiloxane from Preparation Example 2 (vinyl content 0.06 mmoles / g), 8.8 parts of hydrogen-terminated polydimethylsiloxane (Andisil CE-13 chain extender, SiH content 1.37 mmoles / g), 2.0 parts of hydrogen-terminated polydimethylsiloxane with end-hydrogen groups (Andisil XL-1340 crosslinking agent, SiH content 3.0 mmoles / g), 0.15 parts of (S)-5-phenyl-1-pentyn-3-ol (CAS No.: 183904-28-1), and 0.44 parts of boron nitride nanosheets.

[0063] The difference between Example 9 and Example 1 is that: a high thermal conductivity silicone gel for IGBT packaging is composed of component A and component B, and the molar ratio of Si-H and Si-Vi in the high thermal conductivity silicone gel for IGBT packaging is 0.30:1.

[0064] Component A is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (AndisilVS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 200 parts of the modified divinyl-terminated polydimethylsiloxane from Preparation Example 1 (vinyl content 0.08 mmoles / g), and 2 parts of platinum catalyst (Karstedt, 5000 ppm, provided by Dongguan Dongsheng Synthetic Materials Co., Ltd.).

[0065] Component B is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (Andisil VS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 100 parts of the modified divinyl-terminated polydimethylsiloxane from Preparation Example 2 (vinyl content 0.06 mmoles / g), 11.4 parts of hydrogen-terminated polydimethylsiloxane (Andisil CE-13 chain extender, SiH content 1.37 mmoles / g), 2.0 parts of hydrogen-terminated polydimethylsiloxane with end-group hydrogen groups (Andisil XL-1340 crosslinking agent, SiH content 3.0 mmoles / g), 0.15 parts of (S)-5-phenyl-1-pentyn-3-ol (CAS No.: 183904-28-1), and 0.62 parts of boron nitride nanosheets.

[0066] The difference between Example 10 and Example 1 is that: a high thermal conductivity silicone gel for IGBT packaging is composed of component A and component B, and the molar ratio of Si-H and Si-Vi in the high thermal conductivity silicone gel for IGBT packaging is 0.30:1.

[0067] Component A is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (AndisilVS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 100 parts of the modified divinyl-terminated polydimethylsiloxane from Preparation Example 1 (vinyl content 0.08 mmoles / g), and 2 parts of platinum catalyst (Karstedt, 5000 ppm, provided by Dongguan Dongsheng Synthetic Materials Co., Ltd.).

[0068] Component B is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (Andisil VS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 50 parts of the modified divinyl-terminated polydimethylsiloxane from Preparation Example 2 (vinyl content 0.06 mmoles / g), 9.2 parts of hydrogen-terminated polydimethylsiloxane (Andisil CE-13 chain extender, SiH content 1.37 mmoles / g), 2.0 parts of hydrogen-terminated polydimethylsiloxane with end-group hydrogen groups (Andisil XL-1340 crosslinking agent, SiH content 3.0 mmoles / g), 0.15 parts of (S)-5-phenyl-1-pentyn-3-ol (CAS No.: 183904-28-1), and 0.44 parts of boron nitride nanosheets.

[0069] The difference between Example 11 and Example 71 is that component B is made from the following parts by weight of raw materials: 100 parts of divinyl-terminated polydimethylsiloxane (Andisil VS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 100 parts of the modified divinyl-terminated polydimethylsiloxane in Preparation Example 2 (vinyl content 0.06 mmoles / g), 9.7 parts of hydrogen-terminated polydimethylsiloxane (Andisil CE-13 chain extender, SiH content 1.37 mmoles / g), 2.0 parts of hydrogen-terminated polydimethylsiloxane with end-hydrogen groups (Andisil XL-1340 crosslinking agent, SiH content 3.0 mmoles / g), and 0.15 parts of (S)-5-phenyl-1-pentyn-3-ol (CAS No.: 183904-28-1).

[0070] The difference between Example 12 and Example 7 is that component B is made from the following parts by weight of raw materials: 100 parts of divinyl-terminated polydimethylsiloxane (Andisil VS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 100 parts of the modified divinyl-terminated polydimethylsiloxane in Preparation Example 2 (vinyl content 0.06 mmoles / g), 9.7 parts of hydrogen-terminated polydimethylsiloxane (Andisil CE-13 chain extender, SiH content 1.37 mmoles / g), 2.0 parts of hydrogen-terminated polydimethylsiloxane with end-hydrogen groups (Andisil XL-1340 crosslinking agent, SiH content 3.0 mmoles / g), 0.15 parts of (S)-5-phenyl-1-pentyn-3-ol (CAS No.: 183904-28-1), and 1 part of boron nitride nanosheets.

[0071] The difference between Comparative Example 1 and Example 1 is that: an organosilicon gel for IGBT packaging is composed of component A and component B, and the molar ratio of Si-H to Si-Vi in the high thermal conductivity organosilicon gel for IGBT packaging is 0.30:1.

[0072] Component A is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (AndisilVS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g) and 1 part of platinum catalyst (Karstedt, 5000 ppm, provided by Dongguan Dongsheng Synthetic Materials Co., Ltd.).

[0073] Component B is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (Andisil VS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 6.6 parts of hydrogen-terminated polydimethylsiloxane (Andisil CE-13 chain extender, SiH content 1.37 mmoles / g), 2.0 parts of hydrogen-terminated polydimethylsiloxane with end-hydrogen groups (Andisil XL-1340 crosslinking agent, SiH content 3.0 mmoles / g), 0.15 parts of (S)-5-phenyl-1-pentyn-3-ol (CAS No.: 183904-28-1), and 0.25 parts of boron nitride nanosheets.

[0074] The difference between Comparative Example 2 and Comparative Example 1 is that: an organosilicon gel for IGBT packaging is composed of component A and component B, and the molar ratio of Si-H and Si-Vi in the high thermal conductivity organosilicon gel for IGBT packaging is 0.30:1.

[0075] Component A is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (AndisilVS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g) and 1 part of platinum catalyst (Karstedt, 5000 ppm, provided by Dongguan Dongsheng Synthetic Materials Co., Ltd.).

[0076] Component B is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (Andisil VS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 6.6 parts of hydrogen-terminated polydimethylsiloxane (Andisil CE-13 chain extender, SiH content 1.37 mmoles / g), 2.0 parts of hydrogen-terminated polydimethylsiloxane with end-hydrogen groups (Andisil XL-1340 crosslinking agent, SiH content 3.0 mmoles / g), and 0.15 parts of (S)-5-phenyl-1-pentyn-3-ol (CAS No.: 183904-28-1).

[0077] The difference between Comparative Example 3 and Example 1 is that: a high thermal conductivity silicone gel for IGBT packaging is composed of component A and component B, and the molar ratio of Si-H and Si-Vi in the high thermal conductivity silicone gel for IGBT packaging is 0.55:1.

[0078] Component A is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (AndisilVS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 100 parts of the modified divinyl-terminated polydimethylsiloxane from Preparation Example 1 (vinyl content 0.08 mmoles / g), and 2 parts of platinum catalyst (Karstedt, 5000 ppm, provided by Dongguan Dongsheng Synthetic Materials Co., Ltd.).

[0079] Component B is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (Andisil VS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 100 parts of the modified divinyl-terminated polydimethylsiloxane from Preparation Example 1 (vinyl content 0.08 mmoles / g), 22.1 parts of hydrogen-terminated polydimethylsiloxane (Andisil CE-13 chain extender, SiH content 1.37 mmoles / g), 2.0 parts of hydrogen-terminated polydimethylsiloxane with end-group hydrogen groups (Andisil XL-1340 crosslinking agent, SiH content 3.0 mmoles / g), 0.15 parts of (S)-5-phenyl-1-pentyn-3-ol (CAS No.: 183904-28-1), and 0.5 parts of boron nitride nanosheets.

[0080] The difference between Comparative Example 4 and Example 1 is that: a high thermal conductivity silicone gel for IGBT packaging is composed of component A and component B, and the molar ratio of Si-H to Si-Vi in the high thermal conductivity silicone gel for IGBT packaging is 0.55:1.

[0081] Component A is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (AndisilVS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 100 parts of the modified divinyl-terminated polydimethylsiloxane from Preparation Example 2 (vinyl content 0.06 mmoles / g), and 2 parts of platinum catalyst (Karstedt, 5000 ppm, provided by Dongguan Dongsheng Synthetic Materials Co., Ltd.).

[0082] Component B is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane (Andisil VS 200 vinyl-terminated polydimethylsiloxane polymer, vinyl content 0.25 mmoles / g), 100 parts of the modified divinyl-terminated polydimethylsiloxane from Preparation Example 2 (vinyl content 0.06 mmoles / g), 20.5 parts of hydrogen-terminated polydimethylsiloxane (Andisil CE-13 chain extender, SiH content 1.37 mmoles / g), 2.0 parts of hydrogen-terminated polydimethylsiloxane with end-group hydrogen groups (Andisil XL-1340 crosslinking agent, SiH content 3.0 mmoles / g), 0.15 parts of (S)-5-phenyl-1-pentyn-3-ol (CAS No.: 183904-28-1), and 0.5 parts of boron nitride nanosheets.

[0083] Performance testing: Test sample: First, the mold is dried with the following drying parameters: pre-baking at 95℃ for 24 hours to remove residual moisture; when using, mix component A and component B at a mass ratio of 1:1 to obtain the finished high-temperature resistant silicone gel; pour the finished high-temperature resistant silicone gel into the dried mold, and vacuum degas at a pressure of 0.08~0.1MPa for 10 minutes, then cure at 120℃ for 1 hour, and demold.

[0084] 1. Cone penetration test: SN-ZRD2000 cone penetration tester was used for measurement. 2. Electrical strength test method: Tested according to IEC60243-1-2013. 3. Cone penetration change rate test method: After aging at 250℃ for 30 hours, the cone penetration of the sample was measured using SN-ZRD2000 cone penetration tester. The difference between the cone penetration after 250℃ / 30 hours and the initial cone penetration is the cone penetration change rate. The absolute value of the cone penetration change rate ≤15% meets the acceptance standard. 4. Oil seepage performance test: IGBT encapsulation silicone gel of the same mass was placed on filter paper and placed in a vacuum oven at 100℃ and -0.1MPa. The oil seepage performance of the IGBT encapsulation silicone gel sample was observed from 0 to 120 hours. Oil penetration performance is expressed by the oil penetration rate r, r = Dm / D0, where D0 is the initial diameter of the sample; Dm is the diameter of the sample after oil penetration, including the oil trace. 5. Thermal conductivity is determined according to the steady-state heat flow method in ISO 22007-2:2022.

[0085] Table 1: Test parameters of organosilicon gel samples in Examples 1-12 and Comparative Examples 1-4

[0086] As can be seen from Example 1 and Comparative Example 1 and Table 1, the modified bisvinyl-terminated polydimethylsiloxane used in Preparation Example 1 can improve the oil penetration rate, thermal conductivity, heat resistance stability and electrical strength of the organosilicon gel sample.

[0087] Combined with Example 4 and Comparative Example 1 and Table 1, it can be seen that the modified bisvinyl-terminated polydimethylsiloxane used in Preparation Example 2 can improve the oil penetration rate, thermal conductivity, heat resistance stability and electrical strength of the organosilicon gel sample.

[0088] As can be seen from Example 1 and Comparative Examples 1-2 and Table 1, the addition of self-made boron nitride nanosheets can improve the oil penetration rate, thermal conductivity, thermal stability and electrical strength of organosilicon gel samples.

[0089] Combining Examples 7 and 11-12 with Table 1, it can be seen that as the amount of boron nitride nanosheets added increases, the silicone gel sample can improve the oil penetration rate, thermal conductivity, thermal stability and electrical strength, but it will increase its hardness and decrease its cone penetration. Excessive addition will result in the silicone gel sample having a cone penetration of less than 270 mm / 10s, which will not meet the IGBT device packaging standard. The amount of boron nitride nanosheets added should be 0.5-1 parts by weight.

[0090] Based on Examples 1-3 and Comparative Example 3, and referring to Table 1, it can be seen that as the molar ratio of Si-H to Si-Vi increases, the hardness of the silicone gel sample increases rapidly. When the molar ratio of Si-H to Si-Vi is greater than 0.5 / 1, the cone penetration is less than 270 mm / 10 s, which cannot meet the IGBT device packaging standard. The experiments show that a molar ratio of Si-H to Si-Vi of 0.3-0.4:1 is preferable.

[0091] Based on Examples 4-6 and Comparative Example 4, and referring to Table 1, it can be seen that the hardness of the silicone gel sample increases rapidly with the increase of the Si-H to Si-Vi molar ratio. When the Si-H to Si-Vi molar ratio is greater than 0.5 / 1, the cone penetration is greater than 270 mm / 10 s, which does not meet the IGBT device packaging standard. The experiments show that a Si-H to Si-Vi molar ratio of 0.3-0.4:1 is preferable.

[0092] Based on Examples 7, 1, and 4, and in conjunction with Table 1, it can be seen that the use of a mixture of the modified bisvinyl-terminated polydimethylsiloxane in Preparation Example 1 and the modified bisvinyl-terminated polydimethylsiloxane in Preparation Example 2 can better improve the oil penetration rate, thermal conductivity, heat resistance stability, and electrical strength of the organosilicon gel sample.

[0093] Based on Examples 7 and 8-10 and Table 1, it can be seen that the use of modified divinyl-terminated polydimethylsiloxane in Preparation Example 1 and Preparation Example 2 affects the oil penetration rate, thermal conductivity, thermal stability, and electrical strength of the organosilicon gel sample. Given an addition amount of 200 parts by weight of divinyl-terminated polydimethylsiloxane, the total amount of modified divinyl-terminated polydimethylsiloxane in Preparation Example 1 and Preparation Example 2 should preferably be controlled at 150-300 parts by weight, and the mass ratio of modified divinyl-terminated polydimethylsiloxane in Preparation Example 1 to modified divinyl-terminated polydimethylsiloxane in Preparation Example 2 should preferably be controlled at (0.5-2):1.

[0094] In summary, the thermal conductivity of the silicone gel in this invention can reach 0.25-0.27 W / m•K, which is ≥20% higher than that of conventional silicone gels. It also has good thermal stability and electrical strength, and provides better insulation and vibration protection, thereby extending the service life of IGBT devices.

[0095] It should be noted that this specific embodiment is merely an explanation of the technical solution of the present invention and is not intended to limit the present invention. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but as long as they are within the scope of the claims of the present invention, they are protected by patent law.

Claims

1. A high thermal conductivity silicone gel for IGBT packaging, characterized in that: The high thermal conductivity silicone gel for IGBT encapsulation consists of component A and component B, with a Si-H to Si-Vi molar ratio of (0.30-0.50):

1. Component A is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane, 50-200 parts of modified divinyl-terminated polydimethylsiloxane, and 0.5-3 parts of platinum catalyst. Component B is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane, 50-100 parts of... The composition comprises: modified bisvinyl-terminated polydimethylsiloxane, 8-25 parts of hydrogen-terminated polydimethylsiloxane, 1-4 parts of hydrogen-terminated polydimethylsiloxane with hydrogen groups on the end, 0.05-0.25 parts of inhibitor, and 0-2 parts of nano-inorganic filler; wherein the modified bisvinyl-terminated polydimethylsiloxane in components A and B is a bisvinyl-terminated polydimethylsiloxane with at least one of aromatic ring, fluorine element, and aliphatic ring in the side chain and / or a bisvinyl-terminated polydimethylsiloxane with liquid crystal blocks in the main chain.

2. The high thermal conductivity silicone gel for IGBT packaging according to claim 1, characterized in that: The modified bisvinyl-terminated polydimethylsiloxane is made from fluorinated silane monomers, dimethoxysilane monomers, and vinyl silicone oil end-capping agents; the fluorinated silane monomers are any one or more of 3,3,3-trifluoropropylmethyldimethoxysilane, 1H,1H,2H,2H-perfluorooctylmethyldimethoxysilane, and dodecafluoroheptylpropylmethyldimethoxysilane.

3. The high thermal conductivity silicone gel for IGBT packaging according to claim 2, characterized in that: The dimethoxysilane monomer is any one or a combination of multiple types of dimethyldimethoxysilane, isobutylisopropyldimethoxysilane, phenylmethyldimethoxysilane, and cyclohexylmethyldimethoxysilane.

4. The high thermal conductivity silicone gel for IGBT packaging according to claim 2, characterized in that: The vinyl silicone oil end-capping agent is 3-(methoxydimethylsilyl)propyl acrylate and / or vinyldimethylethoxysilane.

5. The high thermal conductivity silicone gel for IGBT packaging according to claim 2, characterized in that: The molar ratio of the fluorinated silane monomer to the dimethoxysilane monomer is 1:(3-7).

6. The high thermal conductivity silicone gel for IGBT packaging according to claim 2, characterized in that: The main chain containing liquid crystal blocks of divinyl-terminated polydimethylsiloxane is made of diacyl chloride-terminated polydimethylsiloxane, dihydroxyl-terminated polydimethylsiloxane, N-(4-hydroxybenzyl)-4-hydroxy-2-trifluoroacetanilide, and vinyl silicone oil end-capping agent.

7. The high thermal conductivity silicone gel for IGBT packaging according to claim 6, characterized in that: The diacyl chloride-terminated polydimethylsiloxane is prepared by a hydrosilylation reaction of dihydro-terminated polydimethylsiloxane and methacryloyl chloride; the vinyl silicone oil end-capping agent is 3-(methoxydimethylsilyl)propyl acrylate and / or vinyldimethylethoxysilane.

8. The high thermal conductivity silicone gel for IGBT packaging according to claim 6, characterized in that: The molar ratio of the diacyl chloride-terminated polydimethylsiloxane to the sum of the molar amounts of the dihydroxyl-terminated polydimethylsiloxane and N-(4-hydroxybenzyl)-4-hydroxy-2-trifluoroacetanilide is (1.01-1.02):1; the molar ratio of the dihydroxyl-terminated polydimethylsiloxane to N-(4-hydroxybenzyl)-4-hydroxy-2-trifluoroacetanilide is (1-3):

1.

9. The high thermal conductivity silicone gel for IGBT packaging according to claim 8, characterized in that: Component A is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane, 100 parts of modified divinyl-terminated polydimethylsiloxane, and 1-2 parts of platinum catalyst; Component B is made from the following raw materials in parts by weight: 100 parts of divinyl-terminated polydimethylsiloxane, 100 parts of modified divinyl-terminated polydimethylsiloxane, 12-16 parts of hydrogen-terminated polydimethylsiloxane, 2.0-2.5 parts of hydrogen-terminated polydimethylsiloxane with hydrogen groups at the ends, 0.10-0.20 parts of inhibitor, and 1-2 parts of nano-inorganic filler; the nano-inorganic filler is boron nitride nanosheets.

10. A method for preparing a high thermal conductivity silicone gel for IGBT packaging according to any one of claims 1-9, characterized in that: Includes the following steps: Step 1: Preparation of modified bisvinyl-terminated polydimethylsiloxane; Step 2, Preparation of component A: 100 parts of bisvinyl-terminated polydimethylsiloxane, 50-200 parts of modified bisvinyl-terminated polydimethylsiloxane, and 0.5-3 parts of platinum catalyst are stirred evenly under an inert atmosphere and then degassed under vacuum to obtain component A. Preparation of component B: 100 parts of bisvinyl-terminated polydimethylsiloxane, 50-100 parts of modified bisvinyl-terminated polydimethylsiloxane, 8-25 parts of hydrogen-terminated polydimethylsiloxane, 1-4 parts of hydrogen-terminated polydimethylsiloxane with hydrogen groups on the end side, 0.05-0.25 parts of inhibitor, and 0-2 parts of nano-inorganic filler were stirred evenly under an inert atmosphere and then vacuum degassed to obtain component B; Step 3: Mix component A and component B evenly to obtain the finished high thermal conductivity silicone gel for IGBT packaging.